Optical observations and spatio-temporal projections of gelatinous zooplankton in the Fram Strait, a gateway to a changing Arctic Ocean - Dmitrii Pantiukhin; Gerlien Verhaegen; Casper Kraan; Kerstin Jerosch; Philipp Neitzel; Henk-Jan T. Hoving; Charlotte Havermans (Frontiers in Marine Science, 2023)
Global warming causes profound environmental shifts in the Arctic Ocean, altering the composition and structure of communities. In the Fram Strait, a transitional zone between the North-Atlantic and Arctic Ocean, climate change effects are particularly pronounced and accelerated due to an increased inflow of warm Atlantic water. Gelatinous zooplankton are known as key predators, consuming a great variety of prey and playing an important role in marine ecosystems. Insufficient knowledge of how gelatinous zooplankton are affected by environmental change has resulted in a notable gap in the understanding of the future state of Arctic ecosystems. We analyzed the diversity and abundance of gelatinous zooplankton down to 2600 m depth and established the first regional baseline dataset using optical observations obtained by the towed underwater camera system PELAGIOS (Pelagic In situ Observation System). Our data estimate the abundance of 20 taxa of gelatinous zooplankton. The most abundant taxa belong to the family of Rhopalonematidae, mainly consisting of Aglantha digitale and Sminthea arctica , and the suborder Physonectae. Using the observational data, we employed a joint species distribution modelling approach to better understand their distributional patterns. Variance partitioning over the explanatory variables showed that depth and temperature explained a substantial amount of variation for most of the taxa, suggesting that these parameters drive diversity and distribution. Spatial distribution modelling revealed that the highest abundance and diversity of jellyfish are expected in the marginal sea-ice zones. By coupling the model with climate scenarios of environmental changes, we were able to project potential changes in the spatial distribution and composition of gelatinous communities from 2020 to 2050 (during the summer season). The near-future projections confirmed that with further temperature increases, gelatinous zooplankton communities in the Fram Strait would become less diverse but more abundant. Among taxa of the Rhopalonematidae family, the abundance of Aglantha digitale in the entire water column would increase by 2%, while a loss of up to 60% is to be expected for Sminthea arctica by 2050. The combination of in situ observations and species distribution modelling shows promise as a tool for predicting gelatinous zooplankton community shifts in a changing ocean.